Linguistic Structural Conceptual Framework of Literary Non-Fiction - Galstyan, Ashot (Տիգրան Մեծ)
This paper is an attempt to study the linguistic layer of the memoir-writing genre primarily as an exploration of linguistic mentality of a person (linguistic person, character), through which both the human being and the social environment become recognisable. This research describes the conceptual framework of the linguistic structure of the literary nonfiction by employing the following two principles: definition of the linguistic complexity of text-writing techniques and presentation of the aesthetic value of these texts. A number of descriptive, stylistic and structural methods employed in the study show that memoir writing undergoes significant changes and enriches itself through various linguistic forms and internal conceptual frameworks. The author‟s presence in the text is often manifested through its original word structure primarily expressed in the common stylistic system of the work. References to time and places in texts present non-fiction character in a new light. The writer‟s primary goal is not enriching the literary language, but ensuring the composition‟s linguistic authenticity and individuality. The flexibility of the genre is enhanced by intertextual manifestations. Lastly, memoir-writing may have a therapeutic effect on the author.
Keywords: Language and Literature